Human relations : - Lamberton, Lowell H. (Glencoe/McGraw-Hill, 2002)
Human Relations: Strategies for Success covers both new and time-tested theories of human relations, and shows the relationship between human relations skills and career success in one-on-one situations, groups, and organizations. Self-esteem, self-awareness, attitude, motivation, and values are covered as the text explores the personal side of human relations and how it relates to management theory. Human Relations: Strategies for Success stresses the human relations skills and management principles essential to functioning successfully in a global business environment.